ANALISIS KESALAHAN BERBAHASA PADA PESERTA â€œMASTER CHEF INDONESIA 2020â€ - Wahyuningsih, Indah; Damai, Peni Nur; Qubro, Khotijatul (University of Brawijaya, 2021)
This research is motivated by the importance of the use of good and correct Indonesian in any context including in electronic media. The purpose of this study is to analyze some of the errors and language errors spoken by participants of Master Chef Indonesia 2020. This study uses descriptive qualitative methods by describing the data obtained in the form of sentences used by Indonesian Master Chef participants. The data source in this study was the participants of the Indonesian Master Chef 2020. The data collection technique was carried out with literature study techniques, namely by (1) watching the Indonesian Master Chef 2020 show again, (2) writing errors in the Master Chef Indonesia 2020 show, (3 ) classifying language errors in Master Chef participants in phonology, morphology, and syntax. The content analysis technique is used to describe the language errors of the participants of the Indonesian Master Chef. Based on the data found, there are several language errors that have been classified, namely language errors (interference) and language errors in the field of linguistics (phonology, morphology, and syntax).